Effect of childbearing-age women’s family status on the health status of three generations: evidence from China - Ding, Yijie; Zhong, Fanglei (Frontiers in Public Health, 2023)
It is widely recognized that inequalities in social status cause inequalities in health.Women in a family often directly influence three generations -women themselves, their children and their parents -yet the effect of women's family status on their own health status and that of the two generations before and after is not clear. Taking data from the China Family Panel Studies, this study used an ordered response model to investigate the effect of childbearing-age women's family status on the health status of three generations. The results showed that increases in childbearing-age women's family status not only improved the health status of women themselves but also significantly affected their parents' and children's health status. The higher the family status of women, the better their own health status and that of their children. Unlike previous studies, however, we found that higher family status did not improve parents' health status but decreased it. The mechanism analysis indicated that women's family status influenced the health status of three generations through economic conditions, resource allocation, and child discipline.The results held after robustness testing. Our findings contribute to knowledge in related fields and provide theoretical support for policies that empower women.